Sravnitel'nyj analiz nekotorych individual'nych osobennostej sportsmenov Irana i Rossii - Golmochammadi, B. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The author has carried out a complex inspection of the athletes-representatives of three kinds of sports and two countries - Iran and Russia.